Black hole entropy from quantum mechanics - Nick Dorey; Rishi Mouland; Boan Zhao (Journal of High Energy Physics, 2023)
Abstract We provide evidence for a holographic duality between superconformal quantum mechanics on the moduli space of Yang-Mills instantons and M-theory in certain asymptotically AdS 7 × S 4 backgrounds with a plane-wave boundary metric. We show that the gravitational background admits a supersymmetric black hole solution whose entropy is precisely reproduced by the superconformal index of the dual quantum mechanics.